Up-regulation of microRNA let-7c by quercetin inhibits pancreatic cancer progression by activation of Numbl - Nwaeburu, Clifford C.; Bauer, Natalie; Zhao, Zhefu; Abukiwan, Alia; Gladkich, Jury; Benner, Axel; Herr, Ingrid (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.11122 Clifford C. Nwaeburu, Natalie Bauer, Zhefu Zhao, Alia Abukiwan, Jury Gladkich, Axel Benner, Ingrid Herr